Dinamika Perkembangan Akuntansi Internasional Pada Negara-Negara Eropa - Dhea Silvia Nandita; Hajjah Aini Makhyarani Nasution; Nirwana Arsyani Zebua; Supranto Prinajaya Siagian; Nurlaila (TAFAQQUH, 2024)
The development of accounting science has triggered the development of more complex accounting standards. The development of accounting standards has led to differences in accounting practices between countries, including European countries. The application of accounting standards in Europe cannot be separated from the influence of the development of American and British accounting systems in European countries. This research aims to see the influence of America and England on the development of accounting in European countries and to compare European countries' accounting practices and systems. The method used in this research is library research, by collecting data from relevant books and journals. This library data is then arranged in a structured manner to obtain research results. The research results show that the European accounting system has been largely influenced by America and England. European countries have absorbed accounting standards in the form of IFRS in their accounting practices. Several European countries have created their own country's accounting standards, but their practices are still adapted to international accounting and IFRS so that there is still harmonization of accounting standards in each European country.